Kedaulatan teritorial negara: kepentingan material dan nilai simbolik - I Gede Wahyu Wicaksana (Masyarakat, Kebudayaan dan Politik, 2016)
This article discusses state’s rights ofterritorial sovereignty, aimed at juxtaposing both the components of material interest and symbolic value. Arguably, states are supposed to be the legitimate owner of the rights of territorial sovereignty, as comprising jurisdiction authority, the right to benefit from natural resources, and control over border. This line of reasoning is consistent with the contemporary socio-political conception expressed by, for example David Miller. Its intellectual explanationshave, at first, been rendered by the statist theory drawn upon three tendencies of utilitarian argument, Kantian and Lockean philosophy. The nationalist theory, however, comes to revise the statist one. To conclude, the article presents some research agendas significant and salient for developing theory of state’s sovereignty in the expanding international system.